Acute toxicity of textile dye Methylene blue on growth and metabolism of selected freshwater microalgae - Krishna Moorthy, Abarna; Govindarajan Rathi, Bhuvaneswari; Shukla, Satya Prakash; Kumar, Kundan; Shree Bharti, Vidya (Environmental toxicology and pharmacology, 2021)
[Display omitted] •Exposure of microalgae Chlorella vulgaris and Spirulina platensis to Methylene blue resulted in acute toxicity.•Growth inhibition rate, pigment and protein content were inhibited due to toxicity.•Inhibition of pigment synthesis was primary reason of toxicity. Microalgae are ecologically important species in aquatic ecosystems due to their role as primary producers. The inhibition of growth of microalgae due to dye pollution results in an upheaval in the trophic transfer of nutrients and energy in aquatic ecosystems. Therefore, this investigation aimed to evaluate the toxicity of a textile dye Methylene blue (MB) on two microalgae viz. Chlorella vulgaris and Spirulina platensis. An exposure of the unialgal populations of both the microalgae towards graded concentrations of the dye showed a concentration-dependent decrease in specific growth rate, pigment and protein content. In the toxicity study of 24 –96-h, following the OECD guidelines 201, the EC50 values of C. vulgaris and S. platensis ranged from 61.81 to 5.43 mg/L and 5.83 to 1.08 mg/L respectively revealing that S. platensis exhibited a higher level of susceptibility towards the dye as compared to C. vulgaris and the latter is more tolerant to the dye toxicity even at higher concentrations. The findings indicate that the response to dye is a species-specific phenomenon. Given the differences in the cell structure and enzymatic pathways in Spirulina platensis (a prokaryote) and Chlorella vulgaris (an eukaryote), the tolerance levels can differ. After 96-h exposure of C. vulgaris to MB (100 mg/L), the chlorophyll-a, b and carotenoid content were reduced 2.5, 5.96 and 3.57 times in comparison to control whereas in S. platensis exposure to MB (10 mg/L), the chlorophyll-a and carotenoid content were reduced 3.59 and 5.08 times in comparison to control. After 96-h exposure of C. vulgaris and S. platensis to the dye (20 mg/L), the protein content was found to be 4.34 and 2.75 times lower than the control. The protein content has decreased in accordance with the increase in dye concentration.